ANALISIS KORESPONDENSI UNTUK PEMETAAN PERSEPSI - Rusgiyono, Agus (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2010)
Correspondence analysis used to investigate the relationship between two or more qualitative variables. This technique could shrink the dimensions of variables and describe the profile vector of rows and columns of a matrix vector data from the contingency table. Target correspondence analysis is to show the relationship variables rows and columns as well as visualization variables in R2-dimensional space, using the Chi square of the distance definition in sub-Euclidean space. Keywords: Profile of Row and Column Vectors, Chi Square Distance, Euclidean Subset